Loss Experience and Emotional Maturity: The Mediating Role of Reflective Functioning - Mchedlidze, Nino; Kalogeropoulos, Dimitra (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to examine the mediating role of reflective functioning in the relationship between loss experience and emotional maturity among adolescents.Methods and Materials: This descriptive correlational study was conducted with a sample of 390 high school students aged 15 to 18 from various regions of Greece, selected using multistage cluster sampling based on the Krejcie and Morgan sample size table. Participants completed the Core Bereavement Items (CBI) to measure loss experience, the Reflective Functioning Questionnaire (RFQ-8), and the Emotional Maturity Scale (EMS). Data analysis included Pearson correlation using SPSS version 27 and Structural Equation Modeling (SEM) using AMOS version 21. Model fit was evaluated using multiple indices including Chi-square, GFI, AGFI, CFI, RMSEA, and TLI.Findings: Results revealed significant negative correlations between loss experience and both reflective functioning (r = –.41, p < .001) and emotional maturity (r = –.47, p < .001). Reflective functioning was positively correlated with emotional maturity (r = .53, p < .001). SEM findings indicated that the structural model had acceptable fit (χ² = 124.65, df = 48, χ²/df = 2.60, GFI = 0.95, AGFI = 0.92, CFI = 0.96, RMSEA = 0.064, TLI = 0.95). Direct effects were significant from loss experience to reflective functioning (β = –0.41, p < .001) and to emotional maturity (β = –0.35, p < .001), and from reflective functioning to emotional maturity (β = 0.42, p < .001). Reflective functioning partially mediated the relationship between loss experience and emotional maturity (indirect β = –0.17, p < .001).Conclusion: Reflective functioning plays a significant mediating role in how adolescents emotionally mature following experiences of loss, suggesting that enhancing reflective abilities may be a viable intervention strategy to foster resilience and emotional growth during adolescence.